Telemedicine in an Outpatient Arthroplasty Setting During the COVID-19 Pandemic: Early Lessons from New York City. Issue 1 (February 2021) - LeBrun, Drake G.; Malfer, Christina; Wilson, Mallory; Carroll, Kaitlin M.; Wang, MS, Victoria; Mayman, David J.; Cross, Michael B.; Alexiades, Michael M.; Jerabek, Seth A.; Cushner, Fred D.; Vigdorchik, Jonathan M.; Haas, Steven B.; et al.
Background: The early months of the coronavirus disease 19 (COVID-19) pandemic in New York City led to a rapid transition of non-essential in-person health care, including outpatient arthroplasty visits, to a telemedicine context. Questions/Purposes: Based on our initial experiences with telemedicine in an outpatient arthroplasty setting, we sought to determine early lessons learned that may be applicable to other providers adopting or expanding telemedicine services. Methods: A cross-sectional study was performed by surveying all patients undergoing telemedicine visits with 8 arthroplasty surgeons at 1 orthopedic specialty hospital in New York City from April 8 to May 19, 2020. Descriptive statistics were used to analyze demographic data, satisfaction with the telemedicine visit, and positive and negative takeaways. Results: In all, 164 patients completed the survey. The most common reasons for the telemedicine visit were short-term (less than 6 months), postoperative appointment ( n = 88; 54%), and new patient consultation ( n = 32; 20%). A total of 84 patients (51%) noted a reduction in expenses versus standard outpatient care. Several positive themes emerged from patient feedback, including less anxiety and stress related to traveling ( n = 82; 50%), feeling more at ease in a familiar environment ( n = 54; 33%), and the ability to assess postoperative home environment ( n = 13; 8%). However, patients also expressed concerns about the difficulty addressing symptoms in the absence of an in-person examination ( n = 28; 17%), a decreased sense of interpersonal connection with the physician ( n = 20; 12%), and technical difficulties ( n = 14; 9%). Conclusions: Patients were satisfied with their telemedicine experience during the COVID-19 pandemic; however, we identified several areas amenable to improvement. Further study is warranted.